Operation of Grid Boosters in Highly Loaded Transmission Grids - Porst, Johannis; Richter, Julian; Mehlmann, Gert; Luther, Matthias (2022 IEEE International Conference on Power Systems Technology (POWERCON), 2022)
In this paper, grid booster operation in highly loaded grid situations is analyzed with respect to power system dynamics. The grid booster consists of fast reacting flexible power units, such as battery energy storage systems and offshore wind parks. Two study cases are simulated representing two highly loaded grid scenarios in the German transmission grid. The paper shows the impact of corrective congestion management with grid boosters on the voltage stability in a large power system and highlights the importance of additional system services, e.g. providing dynamic reactive power reserve. Therefore, additional system services should also be considered for grid booster in highly loaded grid scenarios to successfully perform corrective congestion management. Especially battery energy storage systems proof to be a promising technology for grid booster operations as they can provide different system services depending on the grid situation.<br